Pengaruh net profit margin, current ratio, total assets turn over terhadap harga saham dengan laba sebagai variabel mediasi pada perusahaan di JII70 - Stya, Putri Ade; Kabib, Nur (Journal of Accounting and Digital Finance, 2021)
This study aims to determine the effect of net profit margin, current ratio, total assets turnover on stock prices with profit as a mediating variable in companies listed on the Jakarta Islamics Index70 (JII70) for the 2018-2020 period. This study uses quantitative data in financial statements with path analysis as data analysis. The population used is 70 companies in JII70 with a sample of 150 for three years. The results showed that the variables of net profit margin and return on assets affected stock prices, while the current ratio and total assets turnover did not affect stock prices. The variable net profit margin and total assets turnover affect the return on assets, while the current ratio variable does not affect the asset return. Furthermore, the return on assets variable can mediate the current ratio variable to the stock price but cannot mediate the net profit margin and total assets turnover variable on the stock price.